Strategi Badan Pertanahan dalam Pelayanan Bidang Pembuatan Sertifikat Tanah - Pandri Sugito; Novliza Eka Patrisia (JOPPAS: Journal of Public Policy and Administration Silampari, 2022)
The aim of the research is to find out the strategies implemented by the Land Agency Office in providing services to the community in the field of making land certificates and to find out what factors are hindering the strategy in providing services to the community in Kaur Regency. This study uses a qualitative method. Data collection techniques in this study used observation, interviews and documentation. The results showed that the service for making land certificates carried out by the Kaur District Land Agency Office had been carried out properly, although there were several programs that had not yet been realized. The obstacles that occur in the implementation of making land certificates are not entirely the fault of the Land Agency Office, because the lack of institutions is not a big obstacle for people who want to make land certificates, on the contrary it is the fault of the people who do not follow the applicable regulations, and will impede the work of the Land Agency Office in processing community-owned land certificates. The conclusion that the active role of the community is still needed can improve the deficiencies that are owned by the Kaur District Land Agency Office. Keywords: Land Certificate, Public Service, Service Strategy.